2022
DOI: 10.1371/journal.pone.0279436
|View full text |Cite
|
Sign up to set email alerts
|

Is life satisfaction higher for citizens engaged in political participation: Analysis based on the Chinese social survey

Abstract: Background Political participation is an important component of civil rights. Several studies have shown that citizens’ political participation not only influences the allocation of public resources, but also has a positive correlation with participants’ life satisfaction. Recently, political participation has become increasingly frequent in China; however, the research on Chinese citizens’ political participation and life satisfaction is insufficient. Therefore, this study examined the relationship between po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…In addition, the Taiwanese government at all levels has constructed an online participation platform for public policy that is open to all citizens [22]. Prior studies have indicated that political participation is closely related to life satisfaction, and the life satisfaction of political participants is higher than that of non-political participants [23,24]. Whether citizens have the energy or time to personally participate in environmental protection activities, governments should let them know that their suggestions are taken seriously into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Taiwanese government at all levels has constructed an online participation platform for public policy that is open to all citizens [22]. Prior studies have indicated that political participation is closely related to life satisfaction, and the life satisfaction of political participants is higher than that of non-political participants [23,24]. Whether citizens have the energy or time to personally participate in environmental protection activities, governments should let them know that their suggestions are taken seriously into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation is solidified during the political participation process and is not solely reliant on its outcomes, reflecting what Lane (1988) refers to as procedural utility. By participating politically, individuals exercise their rights, act according to their values, and contribute to society, enhancing the likelihood of experiencing wellbeing and personal satisfaction (Flavin and Keane 2011;Weitz-Shapiro and Winters 2011;Klar and Kasser 2009;Šarkut ė 2017;Shi et al 2022).…”
Section: Subjective Well-being and Political Participationmentioning
confidence: 99%